Kecerdasan Intelektual, Emosional, Spiritual, Motivasi Belajar, dan Pemahaman Akuntansi pada Masa Pandemi Covid-19 - Berlianawati, Ni Luh Putri; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi; Vol 32 No 1 (2022)DO - 10.24843/EJA.2022.v32.i01.p18, 2022)
Accounting students are required to have a high understanding of accounting in order to understand the lecture material well. The purpose of the study is to provide empirical evidence regarding the influence of intellectual, emotional, spiritual intelligence and learning motivation on accounting understanding during the covid-19 pandemic. The research was conducted at the Faculty of Economics and Business, Udayana University. The number of samples used were 78 students. Sampling uses nonprobability sampling method and purposive sampling technique. Data was collected by means of a questionnaire. The analysis technique used is multiple linear regression. The results of the analysis found that intellectual intelligence, emotional intelligence, spiritual intelligence and learning motivation had a positive effect on accounting understanding during the Covid-19 pandemic. Keywords : Intellectual Intelligence; Emotional Intelligence; Spiritual Intelligence; Motivation To Learn; Understanding Of Accounting.